Pendampingan Desa Wisata Bukit Roso Wulan Gunungkidul dalam Implementasi Pemasaran Online Berbasis Website Guna Meningkatkan Kunjungan Wisatawan - Zabidi, Yasrin; Astuti, Marni; Utomo, Bagus Wahyu (Joong-Ki : Jurnal Pengabdian Masyarakat, 2023)
This community service activity aims to assist the management of the Bukit Roso Wulan tourist village in implementing website-based online marketing to increase tourist visits. This activity was carried out because the tourism manager did not know how to promote it online. The target to be achieved is that the management of the Evidence Roso Wulan tourism village is able to create website-based online marketing content and understand the implementation of website-based online marketing. The results or outcomes of this community service activity are in the form of the Bukit Roso Wulan website as an online marketing and promotional medium. The achievement of this activity was that the Bukit Roso Wulan tourism manager could create website-based online marketing content and understand the implementation of marketing, especially website-based online promotions. Keywords: tourist village, marketing online, website, content marketing